Development of Animated Video-Based Learning Media on the Material of Various Types of Jobs for Grade IV Students of SDN 101765 Bandar Setia - Wanda Amelia Purba; Siti Halisya Parapat; Heppy Ariani Harahap; Azwar Siregar; Ardila Salisa Adristi; Eka Yusnaldi (Sean Institute, 2024)
This research aiming to produce a product in the form of learning media, namely animated video- based learning media. Then a media validation test was carried out to determine the feasibility and quality of animated video- based learning media in grade IV elementary school science learning. This type of research is development research or Research and Development (R&D) with the ADDIE model which consists of five steps or stages, namely analysis, design, development, implementation and evaluation. Data collection techniques are by means of interviews, observations, and questionnaires. The results of the validation test by two validators, namely the media expert validator obtained an average of 9 scores interpreted into the very appropriate category, and the material expert validator obtained scores of 9, 2, and 3 in the very appropriate categories. The students ' response to the media obtained 92% results in the very appropriate category. And the teacher's response to learning media obtained a percentage score of 96% in the very appropriate category. Based on the data that has been obtained, it can be concluded that animated video- based learning media in grade IV elementary school science learning is suitable for use in learning activities.